Tra i libri di Isacco Argiro - Gioffreda, Anna (Transmissions, 2020)
This investigation sheds light on Isaac Argyrus and his scholarly work in 14th-century Constantinople on the basis of his book production: it　thus fills a major desideratum of cultural-historical, paleographical, and textual critical studies on the Palaeologan Age. After a brief introduction summing up the state of the art, the available textual sources are discussed in order to define the timeframe of Argyrus' life and to gather all information about him and his career. A complete lists of the manuscript collection copied by Argyrus introduces the pivotal aspect of the research: the analysis of Argyrus' handwriting in relation with the contemporary graphic context. Since Argyrus seems to have mastered two types of handwriting, a formal one and a cursive one, his graphic training must have been based on two differed models: on the one side the hand of his teacher, Nicephorus Gregoras, on the other one a writing style widespread in the XIV century, known as Τῶν῾ Οδηγῶν. The paleographical point of view leads also to the reconstruction of Argyrus' scholarly enviroment, through a detailed description of hands of the scribes who collaborated with him. The writing procedure followed by Argyrus in the composition of his theological treatises eanbles a sound definition of his skills as author. Descriptive reports of each analysed codex conclude the volume. This book shows an example how the use and analysis of material sources, such as manuscripts, can give a innovative and fruitful perspective in investigation about the scholary writings practices in the Byzantine age.